The Protagonist As a Fractured Self: a Study of Taslima Nasreen’S Novel Lajja: Exploring the Fragmented Self in Taslima Nasreen's Novel Lajja (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Religion  is an  ancient  set  of  practices for  attainment  of self-realization. It  is  a part  and  parcel of  human  life. Religion  has always  paved  way for  man’s  journey to  harmony  and integrity. In  Amar  Nath Prasad’s  view, “Religion  is  an  organizing idea  and  it is  the  cohesive force  in  man’s social  structure” ( Prasad  1437). At times  the  differences in  religious  rituals and  practices  instigate the  religious  beings to  turn  into religious  fanatics. Due  to multiplicities  of  religious faiths, the  South-Asian  region is  torn  apart with  the  presence and  emergence  of different  identity  groups. The Indian  subcontinent  in particular  has  been grappling  with  ethnic perplexity. The  events  like demolition  of  Babri Masjid  at  Ayodhya in  India  have further  aggravated  this crisis.